2019
DOI: 10.1364/prj.7.000a56
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of error-disturbance uncertainty relation with continuous variables

Abstract: Uncertainty relation is one of the fundamental principle in quantum mechanics and plays an important role in quantum information science. We experimentally test the error-disturbance uncertainty relation (EDR) with continuous variables for Gaussian states. Two conjugate continuous-variable observables, amplitude and phase quadratures of an optical mode, are measured simultaneously by using a heterodyne measurement system. The EDR with continuous variables for a coherent state, a squeezed state and a thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This relation has been experimentally confirmed recently by using a state-preparation method [28][29][30][31][32], weak probe method [33][34][35][36], continuous-variable entangled states [37,38], and others [39,40]. Subsequently, Branciard [41,42], and Ozawa [43] have considered a rigorous relation reads…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…This relation has been experimentally confirmed recently by using a state-preparation method [28][29][30][31][32], weak probe method [33][34][35][36], continuous-variable entangled states [37,38], and others [39,40]. Subsequently, Branciard [41,42], and Ozawa [43] have considered a rigorous relation reads…”
Section: Introductionmentioning
confidence: 81%
“…that claimed tighter than relation (2) and has been experimentally verified [31,[36][37][38]. Hereafter, we call (3) the Branciard-Ozawa uncertainty.…”
Section: Introductionmentioning
confidence: 89%
“…Gaussian states, such as the squeezed state and the Einstein-Podolsky-Rosen (EPR) entangled state, play essential roles in continu-ous variable (CV) quantum information [29][30][31], where Gaussian states are generated deterministically and information is encoded in the position or momentum quadrature of photonic harmonic oscillators. For example, Gaussian states has been applied in quantum computation [32,33], quantum key distribution [34][35][36], quantum teleportation [37,38], quantum entanglement swapping [39][40][41], quantum dense coding [42,43], and verification of the error-disturbance uncertainty relation [44,45]. Recently, it has been shown that quantum coherence with infinite-dimensional systems can be quantified by relative entropy [46].…”
Section: Introductionmentioning
confidence: 99%
“…Above all, the theory of uncertainty relations [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], the central topic of the paper, has advanced dramatically in the last two decades. Experimental tests of uncertainty relations [20][21][22][23][24][25][26][27][28][29] also have been performed due to the rapid improvement of experimental techniques in recent years. In the paper, we present linear simultaneous measurements of position and momentum with minimum error-trade-off in each minimum uncertainty state.…”
Section: Introductionmentioning
confidence: 99%